Challenging the (dis)ability through grit - life history of elite track and field para-athletes - Pandey, K.; Khusboo, K. (International Journal of Human Movement and Sports Sciences, 2024)
Grit is an impeccable concept which addresses the consistency of interest and perseverance of effort among non-disabled athletes in the existing literature. However, a dearth of research has scrutinised this construct among disabled athletes. The purpose of this research is to explore the challenges of the gritty para-athletes and the reasons behind their grittiness within each narrative type. Two-part life history interviews were conducted with para elite track and field athletes (n=30). The interviews were transcribed and subjected to a dialogical narrative analysis. The speculation was drawn on the stories told by the para-athletes which were based on the grounds of understanding grit and how their life experiences have shaped their grittiness. Five distinct narrative typologies were identified: staying a little longer, quit quitting, a superman story, embracing uncertainty, rising from ashes and everything to me narrative. Grit is inevitable in achieving success but there are many underlying factors which influences grit such as social support, resilience, determination etc. Hence, creating and sharing narratives of gritty para-athletes can help other para-athletes to make sense of their challenges in meaningful and diverse ways. Future implications address the need for the development of the grit-based interventions that can flourish the mental and physical well-being of para-athletes.